Validation of the Bahasa Malaysia Version of the General Attitudes Towards Artificial Intelligence Scale Among Academicians - Azman, Nur Ain; Rasudin, Nur Syahmina; Ismail, Rohani; Abdul Ghafar, Noraini; Shohaimi, Shamarina; Ahmad, Nor Shafrin; Abdul Hamid, Norsiah (Malaysian Journal of Medical Sciences, 2025)
Background: The growing incorporation of artificial intelligence (AI) within academic settings has prompted increased scholarly attention to understanding how academicians perceive its impact. Although the General Attitudes Towards Artificial Intelligence Scale (GAAIS) is a widely recognised instrument for evaluating perceptions of AI, a formally validated version in Bahasa Malaysia has not yet been developed. This study, therefore, sought to adapt and validate the GAAIS in Bahasa Malaysia to assess attitudes toward AI among Malaysian academicians accurately. Methods: A cross-sectional study was conducted among academicians at the Universiti Sains Malaysia Health Campus in Malaysia. A Confirmatory Factor Analysis (CFA) was performed to evaluate the factor structure of the translated scale. Composite reliability (CR) was utilised to assess reliability, whereas convergent validity was determined by calculating the average variance extracted (AVE). Results: The final CFA model confirmed a two-factor structure, retaining 14 out of 20 original items. Factor 1 (Optimism and Benefits) comprised eight items, while Factor 2 (Risks and Ethical Concerns) consisted of six items. The model demonstrated strong fit indices (?²/df = 1.616, TLI = 0.947, CFI = 0.936, RMSEA = 0.073) and high internal consistency (CR values: Factor 1 = 0.899, Factor 2 = 0.888). An AVE of 0.530 for Factor 1 and 0.573 for Factor 2 indicates the convergent validity of the scales. Conclusion: The translated Bahasa Malaysia version of GAAIS is a valid and reliable tool for assessing AI attitudes in general among Malaysian academicians. Its relevance spans multiple academic fields and professional industries, contributing valuable support to ongoing research involving multilingual and multicultural populations.